Emotion recognition development: Preliminary evidence for an effect of school pedagogical practices. (October 2020) - Denervaud, Solange; Mumenthaler, Christian; Gentaz, Edouard; Sander, David
Abstract: While emotion recognition is shaped through social interactions from a child's early years through at least late adolescence, no emphasis has thus far been given to the effects of daily experiences at school. We posited that enriched, more diverse, and less competitive social interactions fostered by some pedagogical practices may contribute to emotion recognition processes in children. Here, we investigated differences in emotion recognition among schoolchildren experiencing the Montessori versus traditional practices. Children performed two tasks; one measuring the impact of social context on fear-surprise perception, and one measuring their bias toward happiness or anger. Results suggest that children experiencing traditional practices show a higher sensitivity to fear-recognition, while children attending Montessori schools show a higher integration of social cues and perceive expressions of happiness for longer durations. Such preliminary findings call for replication and further research to determine which pedagogical features from the Montessori method may explain these effects. Highlights: Emotion recognition differ according to different pedagogical practices. Traditionally-schooled children show higher fear recognition sensitivity. Montessori schoolchildren integrate more social context and are positively biased.